Prognostic role of pretreatment de ritis and neutrophil to lymphocyte ratio in neuroendocrine carcinoma patients (Izmir oncology group study) (Annals of Medical Research, 2021)
Aim: Neutrophil/lymphocyte ratio (NLR) and AST/ALT ratio (De Ritis) were found to be prognostic in several cancers. So, our aim was to investigate the prognostic importance of these parameters and clinicopathological characteristics in patients with neuroendocrine carcinoma (NEC). Material and Methods: We retrospectively reviewed 101 NEC patients diagnosed in the last decade. The values of NLR and De Ritis were assessed at the time of diagnosis and their cut-off values were determined as 5 and 1.04 by receiver operating characteristics analysis. The prognostic role of high or low NLR and De Ritis according to these cut-off values and patient or tumor characteristics on clinical outcome was evaluated. Results: Among 101 patients, 77 were metastatic and 24 were early or locally advanced stage. Almost all patients were death at the time of data analysis (n:90). Twelve patients were treated with adjuvant chemotherapy or radiotherapy while 41 metastatic patients had received first-line chemotherapy. Median overall survival (OS) and progression free survival (PFS) was 7 months and 5 months in NLR low group and 6 months and 4 months in NLR high group (p:0.043, p:0.354), respectively. Median OS was 9 months in De Ritis low group and 5 months in De Ritis high group (p:0.004) while median PFS was 5 and 4 months in De Ritis low and high group of patients (p:0.077). Conclusion: Low De Ritis showed a strong and low NLR showed a weaker association with improved prognosis in patients with NEC.